2012
DOI: 10.1007/jhep01(2012)065
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and field theory in multi-fractional spacetime

Abstract: We construct a theory of fields living on continuous geometries with fractional Hausdorff and spectral dimensions, focussing on a flat background analogous to Minkowski spacetime. After reviewing the properties of fractional spaces with fixed dimension, presented in a companion paper, we generalize to a multi-fractional scenario inspired by multi-fractal geometry, where the dimension changes with the scale. This is related to the renormalization group properties of fractional field theories, illustrated by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
354
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(359 citation statements)
references
References 232 publications
(409 reference statements)
2
354
0
Order By: Relevance
“…(A) Multiscale spacetimes were originally proposed, with quantum gravity in mind, as a class of theories where the renormalization properties of perturbative quantum field theory could be improved, including in the gravity sector [4,32]. Later on, it was shown that the two theories considered in the present paper do not have improved renormalizability [41], while the arguments of [32] still apply to the theory with fractional derivatives.…”
Section: A Dimensional Flow and Multiscale Theoriesmentioning
confidence: 88%
See 3 more Smart Citations
“…(A) Multiscale spacetimes were originally proposed, with quantum gravity in mind, as a class of theories where the renormalization properties of perturbative quantum field theory could be improved, including in the gravity sector [4,32]. Later on, it was shown that the two theories considered in the present paper do not have improved renormalizability [41], while the arguments of [32] still apply to the theory with fractional derivatives.…”
Section: A Dimensional Flow and Multiscale Theoriesmentioning
confidence: 88%
“…In this context, we focus on theories of multiscale spacetimes [4,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. These have been proposed either as stand-alone models of exotic geometry [31,32,40,43] or as an effective means to study, in a controlled manner, the change of dimensionality with the probed scale (known as dimensional flow 1 of these models and of their status).…”
Section: A Dimensional Flow and Multiscale Theoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the theory does not possess any "memory" in its formulation, how then one can make any prediction based on the behavior of geodesics which largely encode the underlying geometry, if the theory has branching geodesics? If, for instance, the action S or the resulting kinematic equations possessed some form "memory" as in the case of systems being modelled by fractional derivatives [72][73][74], then the use of geometric structures with branching geodesics might not pose a serious problem to predictability. Knowing this, one may wish to stay as far away as possible from using metrics that may allow for the possibility of branching geodesics.…”
Section: The Space-time Metric From Variational Principlesmentioning
confidence: 99%